2001
DOI: 10.1177/089686080102103s61
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Standardize Peritoneal Thickness Measurements in Experimental Studies in Rats?

Abstract: Objective The various methods of measuring peritoneal thickness in experimental studies in rats have yielded conflicting results. Also, no standard method exists to assess histologic findings in peritoneal morphology. We therefore undertook the present study to create a reproducible and standard method for assessing rat peritoneal histology in experimental studies. Methods Parietal peritoneal samples from 61 Wistar albino rats were used in the study. Excepting the skin, the whole abdominal wall from each rat w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Mesothelial cell loss and bulging was then evaluated on a semiquantitative three-level scale, as described for SEM. The thickness of submesothelial connective tissue was measured perpendicular to the peritoneal surface 44 in the widest portion cut parallel to the underlying muscle fibers 45 using the software package LAS, v 4.3 (Leica Microsystems, Wetzlar, Germany) at 322Â magnification.…”
Section: Analysis Of Hematoxylin and Eosin Staining Sections By Lightmentioning
confidence: 99%
“…Mesothelial cell loss and bulging was then evaluated on a semiquantitative three-level scale, as described for SEM. The thickness of submesothelial connective tissue was measured perpendicular to the peritoneal surface 44 in the widest portion cut parallel to the underlying muscle fibers 45 using the software package LAS, v 4.3 (Leica Microsystems, Wetzlar, Germany) at 322Â magnification.…”
Section: Analysis Of Hematoxylin and Eosin Staining Sections By Lightmentioning
confidence: 99%
“…Neither other's nor our older studies mention these differences (7,10,11). In our previous study (12), we suggested that both types of sections can be used, but that the horizontal and longitudinal sections showed systematic differences. All samples in a study should be taken using the same section pattern, either longitudinal or horizontal.…”
Section: Discussionmentioning
confidence: 97%
“…The growing interest in the study of the morphology, physiology, and pathophysiology of the peritoneum during PD is therefore not surprising. Different peritoneal tissue samples, including anterior abdominal wall, liver, diaphragm, intestine, and omentum, may be used for this purpose (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Image-Pro Plus version 6.0 (Media Cybernetics, Inc.) was used to analyze the images. ‘Peritoneal thickness’, which indicated the extent of fibrosis, was defined as the thickness of the submesothelial zone measured from the inner surface of the abdominal muscle to the mesothelium (21). The average of five random visual fields was used to quantify the thickness of each section.…”
Section: Methodsmentioning
confidence: 99%